Struktur dan Fungsi Upacara A’dangang di Kawasan Adat Kajang Kabupaten Bulukumba - Nurfadillah Nurfadillah; Risfaisal Risfaisal (Equilibrium: Jurnal Pendidikan, 2017)
A'dangang ceremony is a cultural value in the Kajang Customary Area. The purpose of research to analyze the view of society and function of A'dangang Ceremony to the life of Kajang society. This type of research is descriptive qualitative method, data collection is used by observation, interview, and documentation. Processing techniques and data analysts performed through three stages of data reduction, presentation and draw conclusions. The results show there is a ceremony of death A'dangang, which consists of several levels, namely: a) Dampo Ceremony, b) Lajo-lajo Ceremony. The culture requires the role of government, cultural scientists, academics, journalists, students and all walks of life, to preserve traditional cultural heritage.Keywords: Structure, Ceremony, A'dangang